2010
DOI: 10.1093/annonc/mdq068
|View full text |Cite
|
Sign up to set email alerts
|

Communication about high-cost drugs in oncology—the patient view

Abstract: Women with breast cancer have a strong desire to be active participants in their cancer treatment and wish to be fully informed of potential treatment options, including HCDs. Nondisclosure of information, including HCDs, can result in patient dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 11 publications
1
40
1
Order By: Relevance
“…Although 47% of oncologists indicated that they "always or frequently" discuss costs [24], patient surveys indicate this happens less than 25% of the time [11,23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although 47% of oncologists indicated that they "always or frequently" discuss costs [24], patient surveys indicate this happens less than 25% of the time [11,23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…If there is no opportunity to participate in decision-making processes, patient groups can initiate media campaigns [43]. However, the literature suggest the gaps in patients' knowledge about the funding and decision-making process [29].…”
Section: ] 78%mentioning
confidence: 99%
“…There is evidence to suggest that demand for medicines to treat life-threatening illness is very high regardless of cost [26,29].Survival gain, or gain in quality of life seems to justify even higher cost; at least from the patient perspective. Inequalities regarding willingness-to-pay are related to the financial status of the patient.…”
Section: Treatment Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…8, [29][30][31][32] In a survey on 45 Australian breast cancer patients conducted by Kaser et al, 29 although 96% of patients wanted to discuss an expensive drug as an option with their oncologist, only 28% had discussed high-cost drugs treatment with their oncologist. In another survey on 134 breast cancer patients conducted by Irwin et al, 32 most of the patients (94%) believed that physicians should discuss costs of care with patients, while only 14% of them discussed costs with their doctor.…”
Section: Discussionmentioning
confidence: 99%